URBAN SPACES, RURAL SPACES, AND "OTHER SPACES" IN INDONESIAN FILM FLYERS (1966–1998) - Christopher A. Woodrich (Haluan Sastra Budaya, 2017)
In this article, I examine some three hundred Indonesian film flyers released between 1966 and 1998. I identify three categories of spatial representation: urban spaces, rural spaces, and what I term "other spaces". Urban spaces utilize depictions of high-rises, landmarks, sexuality, crowds, and/or technology as markers of a (Westernized) modernity. Depictions of rural spaces, conversely, emphasize the beauty or dangers of the natural world, as well as strong emotions and primitivism. These depictions suggest the prioritization of an orderly urbanity over a disorderly rurality, with more orderly rural spaces only being locations for travel. "Other spaces", meanwhile, present and/or combine markers of urban and/or rural space, thus forcing viewers to differentiate between place and space and recognize both the constructed nature of space itself and the possible benefits of disorder.